Microfluidic production of bioactive fibrin micro-beads embedded in crosslinked collagen used as an injectable bulking agent for urinary incontinence treatment. (February 2018) - Vardar, E.; Larsson, H.M.; Allazetta, S.; Engelhardt, E.M.; Pinnagoda, K.; Vythilingam, G.; Hubbell, J.A.; Lutolf, M.P.; Frey, P.
Graphical abstract: Abstract: Endoscopic injection of bulking agents has been widely used to treat urinary incontinence, often due to urethral sphincter complex insufficiency. The aim of the study was to develop a novel injectable bioactive collagen-fibrin bulking agent restoring long-term continence by functional muscle tissue regeneration. Fibrin micro-beads were engineered using a droplet microfluidic system. They had an average diameter of 140 μm and recombinant fibrin-binding insulin-like growth factor-1 (α2 PI1-8 -MMP-IGF-1) was covalently conjugated to the beads. A plasmin fibrin degradation assay showed that 72.5% of the initial amount of α2 PI1-8 -MMP-IGF-1 loaded into the micro-beads was retained within the fibrin micro-beads. In vitro, the growth factor modified fibrin micro-beads enhanced cell attachment and the migration of human urinary tract smooth muscle cells, however, no change of the cellular metabolic activity was seen. These bioactive micro-beads were mixed with genipin-crosslinked homogenized collagen, acting as a carrier. The collagen concentration, the degree of crosslinking, and the mechanical behavior of this bioactive collagen-fibrin injectable were comparable to reference samples. This novel injectable showed no burst release of the growth factor, had a positive effect on cell behavior and may therefore induce smooth muscle regeneration in vivo, necessary for the functional treatment of stress and other urinary incontinences. Statement of Significance: Urinary incontinence is involuntary urine leakage, resulting from a deficient function of the sphincter muscle complex. Yet there is no functional cure for this devastating condition using current treatment options. Applied physical and surgical therapies have limited success. In this study, a novel bioactive injectable bulking agent, triggering new muscle regeneration at the injection site, has been evaluated. This injectable consists of cross-linked collagen and fibrin micro-beads, functionalized with bound insulin-like growth factor-1 (α2 PI1-8 -MMP-IGF-1). These bioactive fibrin micro-beads induced human smooth muscle cell migration in vitro . Thus, this injectable bulking agent is apt to be a good candidate for regeneration of urethral sphincter muscle, ensuring a long-lasting treatment for urinary incontinence.